Psychological distress, loneliness, alcohol use and suicidality in New Zealanders with mental illness during a strict COVID-19 lockdown. (July 2022) - Bell, Caroline; Williman, Jonathan; Beaglehole, Ben; Stanley, James; Jenkins, Matthew; Gendall, Philip; Rapsey, Charlene; Every-Palmer, Susanna
Introduction: People with pre-existing mental health conditions may have been disproportionally impacted by the COVID-19 pandemic and associated public health restrictions. In this study, we compared psychological outcomes, experiences and sources of stress over the pandemic lockdown in New Zealanders with and without a previous diagnosis of mental illness. Methods: Two online surveys were conducted in New Zealand over the level 4 lockdown in April 2020 measuring psychological distress, anxiety, well-being, suicidality, alcohol use and subjective experiences. They included 3389 participants, of whom 18.4% reported having been previously diagnosed with a mental illness. Results: During the lockdown, people previously diagnosed with a mental illness had about twice the risk of reporting moderate-high levels of psychological distress (K10 ⩾ 12), at least moderate levels of anxiety (GAD-7 ⩾ 10) and poor well-being (WHO-5 ⩽ 12). They reported increased alcohol use and were about four times as likely to have experienced suicidal thoughts with 3% reporting having made a suicide attempt over the lockdown period. They reported less satisfaction with, and poorer relationships with people in their 'bubble', reduced social contacts and greater loneliness. They also reported higher levels of health and financial concerns. Conclusion: During the COVID-19 lockdown in New Zealand, people with a previous diagnosis of a mental illness were at increased risk of detrimental psychological outcomes. This highlights the importance of recognising this and the challenges people face in pandemics.